2014
DOI: 10.1016/j.jval.2014.08.2170
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mean Overall Survival (OS) and Radiographic Progression Free Survival (RPFS) Based on Matching Adjusted Indirect Comparison of Abiraterone Acetate and Enzalutamide for the Treatment of Castration-Resistant Prostate Cancer in Chemotherapy Naïve Patients

Abstract: cal data for lung metastasis, primary and secondary liver cancer, locally advanced pancreatic cancer population treated with CyberKnife radiation. Searching using Medline, EMBASE, Cochrane Library took place in September 2013. Results: Only one relevant comparative clinical study (matched-pair analysis) met the inclusion criteria, assessing effectiveness and safety of stereotactic radiosurgery and radiofrequency ablation for colorectal liver metastasis. For other neoplasms single-arm studies were found. Compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In these situations, the use of MAIC may be the only way to adjust for cross-trial differences and should be preferred over naïve unadjusted comparisons. Commonly used in observational studies [36], this approach has been successfully applied to previous MAIC analyses of RCTs, such as when placebo comparisons were not available or valid [37], to overcome placebo crossover, or extrapolation beyond study end [32,38]. A week 12, placebo-adjusted comparison was also made.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these situations, the use of MAIC may be the only way to adjust for cross-trial differences and should be preferred over naïve unadjusted comparisons. Commonly used in observational studies [36], this approach has been successfully applied to previous MAIC analyses of RCTs, such as when placebo comparisons were not available or valid [37], to overcome placebo crossover, or extrapolation beyond study end [32,38]. A week 12, placebo-adjusted comparison was also made.…”
Section: Discussionmentioning
confidence: 99%
“…When populations are well matched [8], it is possible to compare long-term data beyond the placebo-controlled phase. This is necessary for chronic conditions such as PsA because the short-term placebo-controlled phase of most RCTs provides only limited data to inform the mid-to long-term treatment choices; indeed, several oncology studies have applied MAIC successfully to long-term patient survival data [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…It appears that this study included an interim report [ 20 ] and a final report [ 14 ] from the COU-AA-301 trial for abiraterone in their indirect treatment comparisons which may have skewed their results. One study [ 17 ] compared mean survival for the two groups and found that the mean survival for enzalutamide (38.7 months; 95% CI = 36.4–40.7) was greater than the mean survival for abiraterone (34.6 months; 95% CI = 31.8–37.8). However, the mean survival time is not informative for understanding the efficacy of a drug on survival as all of the deaths in the study population would have to be observed before a valid mean survival time could be calculated.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mean survival time is not informative for understanding the efficacy of a drug on survival as all of the deaths in the study population would have to be observed before a valid mean survival time could be calculated. Indirect estimates of median radiographic PFS for abiraterone and enzalutamide were similar (both calculated an indirect HR = 0.61; 95% CI = 0.50–0.74) in two studies [ 18 , 19 ] while a third study compared means of radiographic PFS [ 17 ]. We did not include enzalutamide in our indirect treatment comparison analysis of PFS as the AFFIRM trial introduced heterogeneity into the model.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, after week 12, outcomes from the adalimumab arm of ATLAS were directly compared with outcomes from the adjusted and recalculated pooled secukinumab 150 mg arms of MEASURE 1/2. This unanchored (non-placebo-adjusted) MAIC methodology is recommended by NICE in cases when anchored comparisons are not possible ( 14 , 17 , 22 24 ).…”
Section: Methodsmentioning
confidence: 99%